Histological and ultrastructural comparison of cauterization and thrombosis stroke models in immune-deficient mice - Mora-Lee Silvia (Journal of Inflammation, 2011)
Abstract Background Stroke models are essential tools in experimental stroke. Although several models of stroke have been developed in a variety of animals, with the development of transgenic mice there is the need to develop a reliable and reproducible stroke model in mice, which mimics as close as possible human stroke. Methods BALB/Ca-RAG2-/-γc-/- mice were subjected to cauterization or thrombosis stroke model and sacrificed at different time points (48hr, 1wk, 2wk and 4wk) after stroke. Mice received BrdU to estimate activation of cell proliferation in the SVZ. Brains were processed for immunohistochemical and EM. Results In both stroke models, after inflammation the same glial scar formation process and damage evolution takes place. After stroke, necrotic tissue is progressively removed, and healthy tissue is preserved from injury through the glial scar formation. Cauterization stroke model produced unspecific damage, was less efficient and the infarct was less homogeneous compared to thrombosis infarct. Finally, thrombosis stroke model produces activation of SVZ proliferation. Conclusions Our results provide an exhaustive analysis of the histopathological changes (inflammation, necrosis, tissue remodeling, scarring...) that occur after stroke in the ischemic boundary zone, which are of key importance for the final stroke outcome. This analysis would allow evaluating how different therapies would affect wound and regeneration. Moreover, this stroke model in RAG 2-/- γC -/- allows cell transplant from different species, even human, to be analyzed.